Om forholdet mellem skabelse og syndefald hos Grundtvig og Luther - Stokholm, Anja (Grundtvig-studier, 2003)
Om forholdet mellem skabelse og syndefald hos Grundtvig og Luther[Grundtvig and Luther: on the Relationship Between Creation and Fall]By Anja Stokholm Theologically speaking, two circumstances determine human life: on the one side, Creation and the creativity of God, on the other the Fall of Man and human sinfulness. Because God’s good creation is continuous, a positive understanding of the status and existence of natural Man is possible; but because Man is fallen and sin destroys creation, a negative perception of human life must also be acknowledged. Useful comparison may be made between the ideas of Grundtvig and Luther on this ambiguous relationship. One may ask of each: was the image of God in Man destroyed at the Fall or does the likeness of God remain a reality even in the fallen human being? Is it possible for natural Man to understand the Gospel and the Christian life? Can the understanding of the Gospels only have a negative character because it is reached from out of consciousness of sin; or can this understanding have a positive character because, sin notwithstanding, momentary experiencing of the truth of the Gospels may be granted? Are the views of Grundtvig and Luther too divergent to be reconciled?Regin Prenter maintained that their two positions closely corresponded, arguing that Grundtvig consistently developed Luther’s reformatory principles rejecting the possibility of human beings gaining justice or salvation by their own merit, and thereby also accepted that only in consciousness of the fallen condition of the world, the subverted nature of humanity, and sin, could the Gospel’s promises be received. Prenter’s harmonisation of Grundtvig and Luther, however, gives insufficient weight to the differences. Luther contends that the image of God in Man is lost, that Man is wholly sinful and unjustified; that just as inward spirit and outward flesh are discrete and cannot mix so are the justified and the unjustified states; and it follows that the unjustified human being is to be perceived a flesh alone. In so far as continuous creation, and manifestations of the positive such as the human capacity to recognise and comply with the demands of the law, are to be found in the world, these arise not from the inner resources of human beings but from the unmerited gift of God.Grundtvig too emphasises the seriousness and destructive nature of sin; but he insists that a remnant of the image of God persists in humanity - for instance in Man’s capacity to live in faith, hope and love, and to nurture the Word (that is, speech); and that its manifestation is a token of God’s continuing, and good, creation. Crucially important is Grundtvig’s conception that the image of God is located in the human heart, for this implies that goodness and the positive phenomena of creation express human life and nature in their true and proper form, and thus Grundtvig is able to identify natural human life, governed by the heart, as a positive context within which the word of the Gospel is indeed comprehensible. In differentiation, then, from Luther, Grundtvig maintains that natural Man also has a spirit and can be the agent of love and of goodness.Is this position incompatible with Luther’s doctrine on justification? Does the notion of goodness imply that Man can and must contribute to his own salvation? Grundtvig is careful to maintain that positive qualities such as love and goodness are a creation of God in Man, not an autonomous human achievement; and that the grace of God’s continuing creation in Man does not render salvation unnecessary. Man still needs the redeeming creation of Christ.Thus there are considerable differences between Grundtvig and Luther; but Grundtvig’s ideas are to be seen as a renewal and an independent continuation of Luther’s principal doctrine: that God alone can accomplish salvation. Yet acknowledgement and awareness of the differences, which arise in part through the different times and circumstances in which these independent thinkers worked, is conducive to a productive dialogue between the two.